2023
DOI: 10.3390/ijms24054405
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Metabolic Parameters, Leptin and the SGLT2 Inhibitor Empagliflozin among Patients with Obesity and Type 2 Diabetes

Abstract: Obesity is a major public health problem worldwide, and it is associated with many diseases and abnormalities, most importantly, type 2 diabetes. The visceral adipose tissue produces an immense variety of adipokines. Leptin is the first identified adipokine which plays a crucial role in the regulation of food intake and metabolism. Sodium glucose co-transport 2 inhibitors are potent antihyperglycemic drugs with various beneficial systemic effects. We aimed to investigate the metabolic state and leptin level am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Metformin inhibits leptin production and stimulates adiponectin production along with the activation of adenosine monophosphate-activated protein kinase (AMPK), which in turn inhibits mTOR [ 39 , 48 , 49 ]. Sitagliptin, pioglitazone, liraglutide, dapagliflozin, and empagliflozin have been found to reduce leptin levels [ 46 , 50 ]. Pioglitazone and dapagliflozin increase adiponectin concentrations [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin inhibits leptin production and stimulates adiponectin production along with the activation of adenosine monophosphate-activated protein kinase (AMPK), which in turn inhibits mTOR [ 39 , 48 , 49 ]. Sitagliptin, pioglitazone, liraglutide, dapagliflozin, and empagliflozin have been found to reduce leptin levels [ 46 , 50 ]. Pioglitazone and dapagliflozin increase adiponectin concentrations [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sitagliptin, pioglitazone, liraglutide, dapagliflozin, and empagliflozin have been found to reduce leptin levels [ 46 , 50 ]. Pioglitazone and dapagliflozin increase adiponectin concentrations [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DM triggers renal steatosis and lipotoxicity by inhibiting PPARα and PPARγ lipolytic [8,9,33,34], whilst increasing SREBP-1 lipogenic molecules [10,11], which then provoke chronic renal inflammation by augmenting renal TNF-α, IL-1β, and IL-6 levels, and reducing the potent anti-inflammatory cytokine, IL-10 [12,13]. The levels of several renal adipokines are likewise altered in DN, and renal inflammation is aggravated by a substantial decrease in adiponectin [14,35] that coincides with increases in leptin [15,36] and resistin [16,37] levels. Chronic renal oxidative stress and inflammation subsequently trigger apoptosis through TGF-β-mediated activation of Casp-3 [17,18], with glomerulopathy and tubular damage that are manifested by albuminuria and decreased GFR [38,39], and by increasing renal expression of NGAL and KIM-1 [4,40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperglycaemia and dyslipidaemia exacerbate renal inflammation by increasing the production of pro-inflammatory cytokines, such as interleukin (IL)-1β, IL-6, and tumour necrosis factor (TNF)-α, while reducing the antiinflammatory cytokine, IL-10 [12,13]. Renal steatosis also reduces adiponectin [14], and elevates leptin [15] and resistin production in renal tissues [16]. Persistent oxidative stress and inflammation then promote cell apoptosis by upregulating transforming growth factor-β (TGF-β) with caspase-3 (Casp-3), thus aggravating glomerular and tubular damage [17,18].…”
Section: Of 17mentioning
confidence: 99%
“… 68 , 71 , 72 A recent clinical study showed that empagliflozin significantly reduced leptin levels compared with other glucose-lowering drugs used to treat patients with obesity and T2DM, such as biguanides and sulfonylureas. 73 In addition, leptin levels are proportional to adiposity, and SGLT-2 may reduce leptin secretion via its weight-loss effect. 74 As leptin is a major contributor to obesity and elevated blood pressure, leptin may be a potential target for SGLT-2 inhibitors in the treatment of obesity-associated hypertension.…”
Section: Obesity-related Hypertension Sglt-2 Inhibitors and Hyperlept...mentioning
confidence: 99%